ON OF AIR POLLUTION WITH INHALATION ANESTHETICS AND DISINFECTANTS IN OPERATING ROOMS - N. A. Trekova; L. G. Petrosyan; B. A. Akselrod; A. A. Ivanov (Вестник анестезиологии и реаниматологии)
At present levels of air pollution with inhalation anesthetics and disinfectants in operating rooms as well as protection from their unfavorable effect on health and professional activities of the surgical personnel are underexplored. Goal of the study: to evaluate the efficiency of ORUB-3-5-KRONT air recirculator and irradiator for air cleansing from inhalation anesthetics and other organic compounds in operating rooms when using disposable air carbon filters of FUS-KRONT. Materials and methods. During the main stages of anesthesia and operation the content of sevoflurane, inhalation anesthetic and disinfectant of DeziceptI OP for treatment of surgical field was tested during 31 surgeries during operation of the wall mounted air recirculator-irradiators and without them (control group). Kolion 1B gas analyzer was used for online monitoring of the organic compounds concentration in the air of the operating room. Results. Comparative analysis has proved that during all stages of general inhalation anesthesia and surgery the sevoflurate concentration was 2.0-3.5 fold higher with no protection used compared to operation of air recirculator and it was above the ultimate permissible concentrations as per international standards. Treatment of surgical field by an antiseptic caused the up to 10-fold increase of organic substances in the air. The concentration of disinfectants reduced by 90% 2.5 times faster under operation of air recirculators compared to spontaneous cleansing. Conclusion: ORUB-3-5-KRONT air recirculator and irradiator equipped by disposable air carbon filters of FUS-KRONT reduces the content of sevoflurane in the air of operating rooms during anesthesia and surgical operation down to recommended ultimate permissible concentrations and provides fast cleansing of the air in the operating room from organic substances after treatment of the surgical field by an antiseptic.